Chasing icebergs : how frozen freshwater can save the planet - Birkhold, Matthew H. (Pegasus Books, 2023)
"Harvesting icebergs for drinking water is not a new idea. But for the first time in human history, doing so on a massive global scale is both increasingly feasible and necessary for our survival. Chasing Icebergs delivers a kaleidoscopic history of humans' relationship with icebergs, and offers an urgent assessment of the technological, cultural, and legal obstacles we must overcome to harness this freshwater resource"--